2005
DOI: 10.1186/1471-2164-6-179
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis reveals a conserved family of actin-like proteins in apicomplexan parasites

Abstract: Background: The phylum Apicomplexa is an early-branching eukaryotic lineage that contains a number of important human and animal pathogens. Their complex life cycles and unique cytoskeletal features distinguish them from other model eukaryotes. Apicomplexans rely on actinbased motility for cell invasion, yet the regulation of this system remains largely unknown. Consequently, we focused our efforts on identifying actin-related proteins in the recently completed genomes of Toxoplasma gondii, Plasmodium spp., Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 60 publications
4
73
0
Order By: Relevance
“…Using a conditional knockout for act1 it was demonstrated that no ACT1 filament formation can occur as early as 48 h after removal of act1 [28]. Finally, although apicomplexans possess actin-like proteins, it is unlikely that they can compensate for ACT1 and form filaments [27, 51]. Here, we performed a careful quantification of actin levels at different time points in the act1 conditional knockout and find that actin is still detectable at 48 h, but fully depleted by 96 h after induction with rapamycin.…”
Section: Discussionmentioning
confidence: 99%
“…Using a conditional knockout for act1 it was demonstrated that no ACT1 filament formation can occur as early as 48 h after removal of act1 [28]. Finally, although apicomplexans possess actin-like proteins, it is unlikely that they can compensate for ACT1 and form filaments [27, 51]. Here, we performed a careful quantification of actin levels at different time points in the act1 conditional knockout and find that actin is still detectable at 48 h, but fully depleted by 96 h after induction with rapamycin.…”
Section: Discussionmentioning
confidence: 99%
“…This protein complex facilitates endosomal protein sorting by stimulating Arp2/3 to nucleate F-actin on endosomal membranes. Since the Arp2/3 nucleator complex is absent in apicomplexan parasites [61], the classical endosome-to-PM recycling pathway might have been lost in these organisms and an alternative form of PM recycling, possibly dependent on microtubules, has evolved in apicomplexan parasites. Nonetheless, it would be interesting to investigate the role of actin in endosomal trafficking in apicomplexan parasites.…”
Section: Endosomal Factors Involved In the Biogenesis Of Secretory Ormentioning
confidence: 99%
“…The myosin family has several additional members whose roles in cytoskeletal development and cell division have yet to be evaluated (Foth et al, 2006; Heintzelman, Schwartzman, 2001; Polonais et al , 2011a; Santos et al , 2009). In addition, a role for IMC assembly was suggested for ALP1 (Gordon et al, 2008), which is also a member of an extensive family (Gordon, Sibley, 2005). Although the function of these myosins and actin-like proteins has not been determined, it is likely that some of these function in cell division.…”
Section: Mechanistic Insights From Disruption Of Cytoskeletal Compmentioning
confidence: 99%